2014
DOI: 10.1074/jbc.m114.550046
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of the Adenoviral VA RNAI Central Domain Structure Reveals Minimum Requirements for RNA-mediated Inhibition of PKR

Abstract: Background: Adenoviruses use the short non-coding transcript VA RNA I to inhibit host antiviral kinase PKR. Results: VA RNA I contains a pH-and Mg 2ϩ -sensitive tertiary structure that, unexpectedly, is not required for PKR inhibition. Conclusion: Structural requirements for an RNA inhibitor of PKR are simpler than appreciated previously. Significance: These findings explain how non-coding RNAs of varied sequence and structure can efficiently inhibit PKR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
49
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(52 citation statements)
references
References 39 publications
2
49
1
Order By: Relevance
“…We found that the addition of an N-terminal SUMO (smt3) tag allowed soluble expression of both shorter constructs. Importantly, the addition of the SUMO tag had no discernible effect on hPKR activation or inhibition by poly(rI:rC) dsRNA and Ad2 VA RNA I (30,32), respectively (Fig. 2, A and B).…”
Section: Design and Expression Of Idl Deletion Pkr Variants-hpkrmentioning
confidence: 99%
See 3 more Smart Citations
“…We found that the addition of an N-terminal SUMO (smt3) tag allowed soluble expression of both shorter constructs. Importantly, the addition of the SUMO tag had no discernible effect on hPKR activation or inhibition by poly(rI:rC) dsRNA and Ad2 VA RNA I (30,32), respectively (Fig. 2, A and B).…”
Section: Design and Expression Of Idl Deletion Pkr Variants-hpkrmentioning
confidence: 99%
“…RNA in Vitro Transcription and Purification-A truncated form of human adenovirus type 2 (Ad2) VA RNA I (94 nucleotides), which retains full wild-type activity but lacks the entire terminal stem ("TS⌬21") and a short sequence in the apical stem ("A2dl2") was in vitro transcribed using T7 RNA polymerase under previously established optimal conditions (31,32). HIV-1 TAR RNA (59 nucleotides) was also prepared by T7 RNA polymerase run-off transcription using established conditions (33,34).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…PKR is activated by binding to dsRNA, originating from viral transcription, whereupon it phosphorylates the translation initiation factor eIF2 to inhibit protein synthesis in virus-infected cells (de Haro et al 1996). The cytoplasmic VA RNA I competes with dsRNA for binding to PKR but, instead of stimulating, inhibits activation of PKR, thereby enabling viral protein synthesis (Mathews and Shenk 1991;Wilson et al 2014). VA RNAs can also act as substrates for the RNase III enzyme Dicer, with the products being incorporated into functional Argonaute (AGO)-containing RNA-induced silencing complexes (RISCs) (Aparicio et al 2006(Aparicio et al , 2010.…”
mentioning
confidence: 99%